Identification and Functional Analysis of the G1 Phase Cyclin Dependent Kinase Gene Hc-CDK6 in Pearl Mussels (Hyriopsis cumingii) - Feng, ShangLe; Li, XueNan; Wang, He; Li, WenJuan; Bai, ZhiYi (Frontiers in Marine Science, 2022)
Cyclin dependent kinase 6 (CDK6) is a serine/threonine kinase that plays important roles in cell cycle progression and differentiation. In this study, full-length cDNA of Hc-CDK6 was obtained from freshwater pearl mussels (Hyriopsis cumingii, Hc) with 3´,5´ rapid-amplification of cDNA ends (RACE). The Hc-CDK6 expression profiles were analyzed with quantitative real-time PCR and in situ hybridization. The function of the Hc-CDK6 gene was studied with both RNA interference (RNAi) and overexpression in H. cumingii. Hc-CDK6 was found to encode 331 amino acids and to have a CDK4/6-like serine/threonine kinase catalytic structural domain. In terms of the amino acid sequence, the protein Hc-CDK6 was most closely related to its homolog in Crassostrea gigas, with a similarity of 75.23%. Hc-CDK6 was expressed in all examined tissues (adductor, foot, visceral mass, gill, outer mantle, inner mantle and gonads), and the highest expression was observed in the gonads (P<0.05). The relative expression of Hc-CDK6 increased during embryonic development, and was higher in the blastocyst and gastrulation stages, which were characterized by rapid division and differentiation. Hc-CDK6 showed hybridization signals in all parts of the mantle. After knockdown of Hc-CDK6 through RNAi, a significant decrease in CDK6 expression was found, and the percentage of cells in G0/G1 significantly increased. Overexpression of Hc-CDK6 in mantle cells increased the proliferation of cultured cells (P<0.05). Hc-CDK6 appeared to promote the cell cycle in H. cumingii, and overexpression of Hc-CDK6 promoted mantle cell proliferation. The functional study of this gene may provide new ideas for solving the problem of slow proliferation of shellfish cells in in vitro culture.